Epilepsy as a Disease Affecting Neural Networks - Pretika Prameswari (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
This research aims to investigate and analyze epilepsy as a disease that affects nervous tissue. The approach used in this research is a qualitative approach with literature study. Epilepsy is a neurological disease characterized by recurrent epileptic seizures. This disease affects the nerve tissue in the brain, causing disruption in the normal functioning of the nervous system. This research method includes analysis of literature studies relevant to the topic of epilepsy and its effect on neural networks. Various sources such as scientific journals, articles and books related to epilepsy and the nervous system were used in this research. Data collected through literature studies were then analyzed qualitatively to identify patterns, trends and important findings related to epilepsy as a disease that affects nervous tissue. The results of this study suggest that epilepsy can affect various aspects of neural networks, including brain structure, synapse connectivity, and electrical activity. Epileptic seizures that occur can cause damage to nerve tissue and affect overall brain function. Apart from that, epilepsy can also affect the development and growth of nervous tissue in children. These findings have important implications in the development of epilepsy diagnosis and treatment. With a better understanding of how epilepsy affects neural networks, we can develop more effective approaches to diagnosing this disease and design more appropriate treatment strategies. In addition, this research also provides additional insight into the pathophysiological mechanisms of epilepsy and strengthens our understanding of the complexity of this disease. This research highlights the importance of understanding epilepsy as a disease that affects neural networks. A qualitative approach with literature studies has helped reveal the relationship between epilepsy and neural networks, as well as the importance of diagnosis and treatment. Further research is needed to deepen our understanding of epilepsy and its effects on neural networks in more detail.